Primary Hyper Parathyroidism - Chowdhury, Md Faizul Islam; Khandaker, MAK; Zaid, Hossain M; Saha, Biplab Kumar; Hossain, Md Murad (Journal of Medicine, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3329/jom.v7i1.1361 J MEDICINE 2006; 7 : 39-41